Development of flexible, stable, and efficient inverted organic solar cells harvesting light in all directions. (5th December 2019) - Hilal, Muhammad; Han, Jeong In
Abstract: In this work, we designed low-cost, liquid-free, efficient, and highly flexible fiber-shaped inverted structure organic solar cells (FOSCs) over a flexible polyethylene terephthalate (PET) monofilament substrate. We also prepared a graphene–ZnO (G-ZnO) composite, wherein G sheets were compacted into a bunched-up structure through the binding force of Zn atoms with the C atoms of G. This composite was then utilized as a bifunctional layer i.e. electron transport and downconversion spectral in the FOSCs. The FOSCs based on the G-ZnO (D-1) demonstrated a power conversion efficiency (PCE) of 2.13% out of which 4.89% and 5% was retained after 8000 times bending and 120 h storage in ambient environmental conditions, respectively. The non-G-ZnO FOSCs (D-2) demonstrated a PCE of 1.78% and retained 5% and 6% of the initial value after 6000 bends and 48 h of storage in ambient environmental conditions, respectively. This better performance of D-1 compared to that of D-2 is due to the interfacial functionalization of G-sheets and ZnO nanoparticles inside the G-ZnO composite. Because of these interfacial chemical bonds, the G sheets were in close contact with each other and attached firmly through the ZnO molecules. As a result, these compacted G layers could serve as a strong barrier resisting the penetration of water molecules inside the device, thereby leading to an improved lifetime for the device. Additionally, the longitudinal and cross linkage of G-sheets could improve the mechanical properties of the G-ZnO composite, which in turn enhanced the flexibility of D-1. Finally, these interface functionalizations could work as linking bridges, providing an additional pathway for the transportation of free charge carriers. Therefore, D-1 demonstrated a higher Jsc by collecting a greater number of charges at the electrode compared to D-2, because the latter lacked similar functionalization. Graphical abstract: Image 1 Highlights: Fiber-shaped OSCs with high mechanical flexibility, environmental stability, and harvesting light in all directions. Low cost and easy synthesis method for the development of high electrical conducive graphene—ZnO (G—ZnO) composite. The newly developed G—ZnO composite employed as electron transport and Downconversion spectral layer in the FOSCs. The impressive performances of constructed FOSCs are attributed to the interface chemistry of the developed G—ZnO layer. The types of chemical bonds formation at the interface of G—ZnO was confirmed based on the XRD, XPS and Raman spectroscopy.